The Analytical Procedures of Grounded Theory Methodology in Research on the Human Body - Byczkowska-Owczarek, Dominika (Przegląd Socjologii Jakościowej, 2019)
The purpose of this article is to look into the problem of grounded theory methodology (GTM) application in social research on the human body. First, the theoretical roots of GTM in symbolic interactionism are enumerated and their consequences for applying the research strategy are described. The author presents examples of her research as an illustration of how GTM procedures enable the researcher to ingrain the body in social processes, and explains what it actually means to embed physical body in social phenomena and processes. The conclusions concerning the practice of GTM research are based on a series of empirical studies conducted by the author in the fields of dance, physical therapy, and medical work. The author argues that GTM expounds on specific procedures, which offer both methodological discipline and flexibility that is necessary for studying as challenging phenomenon as that of the human body.